Obesity, malnutrition, and the prevalence and outcome of hypertension: Evidence from the National Health and Nutrition Examination Survey - Zhang, Heng-Zhi; Wang, Yi-Han; Ge, Ying-Lin; Wang, Shu-Yu; Sun, Jin-Yu; Chen, Lu-Lu; Su, Shuang; Sun, Ying (Frontiers in Cardiovascular Medicine, 2023)
Background Nutritionally unhealthy obesity is a newly introduced phenotype characterized by a combined condition of malnutrition and obesity. This study aims to explore the combined influence of obesity and nutritional status on the prevalence and outcome of hypertension. Methods Participants collected from the National Health and Nutrition Examination Survey (NHANES) database were divided into four subgroups according to their obesity and nutritional conditions, as defined by waist circumference and serum albumin concentration. The lean-well-nourished was set as the reference group. Logistic regression models were applied to evaluate the hypertension risk. Kaplan–Meier analysis and Cox proportional hazard regression models were used to assess the survival curve and outcome risk of participants with hypertension. Results A total of 28,554 participants with 10,625 hypertension patients were included in the analysis. The lean-malnourished group showed a lower hypertension risk (odds ratio [OR] 0.85, 95% confidence interval [CI]: 0.77–0.94), while the obese-well-nourished condition elevated the risk (OR 1.47, 95% CI: 1.3–1.67). Two malnourished groups had higher mortality risks (HR 1.42, 95% CI: 1.12–1.80 and HR 1.31, 95% CI: 1.03–1.69 for the lean and obese, respectively) than the reference group. The outcome risk of the obese-well-nourished group (HR 1.02, 95% CI: 0.76–1.36) was similar to the lean-well-nourished. Conclusion Malnutrition was associated with a lower risk of developing hypertension in both lean and obese participants, but it was associated with a worse outcome once the hypertension is present. The lean-malnourished hypertension patients had the highest all-cause mortality risk followed by the obese-malnourished. The obese-well-nourished hypertension patients showed a similar mortality risk to the lean-well-nourished hypertension patients.